Conceptualizing the Digital Pedagogy in Arts Higher Education: Examining the Roles of Training, Technology Support, and Teacher Mindsets - Tai, Ge; Nasir, Nadia Binti Mohd (South Asian Journal of Social Sciences and Humanities, 2024)
In this concept paper, the propositions for incorporating professional development, ICT awareness,  and technical support to introduce technology incorporation practices among College of Arts  instructors are discussed. Drawing from past research in practice, this study’s conceptual  framework posits value and ability beliefs as the mediators of technology integration practices.  This research establishes professional development, ICT knowledge, and technical assistance as  determinants of technology integration practices for learning in the study and looks at the value  and ability beliefs and their impact on the instructors’ decision to integrate technology into the  teaching practice. This work contributes to the generation of practical and theoretical knowledge  for designing effective technology integration in arts education practices, underscoring the  centrality of the multipronged perspectives of instructors’ belief, content, and practice knowing.  In this case, this study seeks to improve the quality of arts education and better prepare College of  Arts students for the job market of the still-growing technology focused era by raising the level of  preparedness for integrating technology into lessons of the College of Arts instructors.
Keywords: Art teachers; Information communication technology; ICT; Knowledge; Technology integration; and Teaching process